2021
DOI: 10.3389/fphys.2021.635132
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability During a Standard Dive: A Role for Inspired Oxygen Pressure?

Abstract: Introduction: Heart rate variability (HRV) during underwater diving has been infrequently investigated because of environment limitations and technical challenges. This study aims to analyze HRV changes while diving at variable hyperoxia when using open circuit (OC) air diving apparatus or at constant hyperoxia using a closed-circuit rebreather (CCR). We used HRV analysis in time and frequency domain adding nonlinear analysis which is more adapted to short-time analysis and less dependent on respiratory rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Moreover, O 2 breathing goes beyond mere therapeutic use. Breathing an O 2 mixture at different concentrations, either hypoxic or hyperoxic, has been used for sport training [ 9 ], cardiovascular conditioning [ 10 , 11 ], or before extreme environmental exposure, such as SCUBA diving [ 12 , 13 ], military high-altitude free fall [ 14 , 15 ], or space flight [ 16 , 17 ], to avoid the occurrence of decompression sickness (DCS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, O 2 breathing goes beyond mere therapeutic use. Breathing an O 2 mixture at different concentrations, either hypoxic or hyperoxic, has been used for sport training [ 9 ], cardiovascular conditioning [ 10 , 11 ], or before extreme environmental exposure, such as SCUBA diving [ 12 , 13 ], military high-altitude free fall [ 14 , 15 ], or space flight [ 16 , 17 ], to avoid the occurrence of decompression sickness (DCS).…”
Section: Introductionmentioning
confidence: 99%
“…Large deviations from normoxia generally lead to increased oxidative stress, while the slight modulation of oxygen levels can enhance the antioxidant defenses [ 1 , 49 ]. We therefore investigated extremes, from 0.1 ATA (Summit of Kilimanjaro (5791 m)) to 2.5 ATA (therapeutic hyperbaric oxygen sessions), and several intermediate oxygen levels relevant to high-altitude exposure (2400 to 2700 m) or O 2 levels used during closed circuit rebreather (CCR) diving—either in recreational, technical, or military diving (0.15, 0.30, 1.0, and 1.4 ATA) [ 12 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each diver wore a chest elastic belt sensor Polar H10 connected to the Polar Unite watch (Polar Electro Oy, Kempele, Finland) to record the R-to-R interval at a 1000 Hz sampling frequency. The validity of this device for HRV measurement has already been demonstrated in several studies [ 22 , 34 ]. The resting baseline was recorded in a sitting position, after ten minutes at rest, before the first dive and 24 h after the last day for ten minutes.…”
Section: Methodsmentioning
confidence: 82%
“…There are marked changes in autonomic cardiac activity during and after scuba diving with a predominance of PNS activity [ 20 , 21 ]. There are complex and sometimes conflicting additional ANS modulations, and CCR diving seems to provoke a different HRV response in divers as compared to OC diving [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that the administration of exogenous eCB (i.e., phytocannabinoids) in studies of humans and animals, exerts a chronotropic influence on heart rate [ 10 , 11 , 12 ]. At this point, it is useful to bring into mind that heart rate variability (HRV) is sensitive to changes in autonomic nervous system (ANS) activity (i.e., changes in the sympathetic nervous system (SNS) and parasympathetic nervous system (PNS)) associated with stress [ 12 , 13 , 14 ]. Neuroimaging studies suggested that HRV may be linked to cortical regions (e.g., the ventromedial prefrontal cortex) that are involved in stressful situation appraisal.…”
Section: Introductionmentioning
confidence: 99%